Mobilitas Sirkuler Daya Faktor-faktor Yang mempengaruhinya Di Desa Sidorejo Kec Ponjong Kab Gunung Kidul = Circular Mobility And The Factors Influencing It In Sidorejo Village Ponjong Sub District Gunung Kidul Regency - Utami A Yulianti; Mas Sadjono; Slamet Hartono (Agro Ekonomi, 2003)
The research aims to find out the factors affecting the circular mobility and the impact of circular mobility on farm production and farmers income.Primary data are .from sample farmers migrant and non migrant. The sample size is 70. The data analyzed by logit model and by difference mean testThe result showed. the affecting factors to circular mobility are. ll. The rural income is negatif flea. 2). Land size is posilif affect 3). wage ratio urban rural negatif affect, The impact of circular mobility increas production and .farmer income. The income ofmigrant familly is Rp -1722611 per year and Rp 2848168 per year for non migrant. The mobility activity contributed higher peoduction and income for migran.